STRUKTUR MODAL DALAM MEMODERASI PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2016-2019) - Mahatma Maghfirandito; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2022)
This research was conducted because of the research gap phenomenon or the different results of previous studies. Summary of research gaps sourced from related research journals. This study aims to determine the effect of capital structure in moderating the effect of profitability, firm size and firm growth on firm value. The sample used in this study used manufacturing companies in 2016-2019 with a total sample of 69 samples. Sampling was based on a purposive sampling method that followed certain criteria. The type of data used in this study is secondary data, in the form of the company's annual report. This study uses a quantitative descriptive method to analyze the data. The results of this study indicate that profitability and firm size have a significant and positive effect on firm value, while firm growth has no significant effect on firm value. In addition, there is a significant and positive effect between the interaction of profitability with capital structure on firm value and a significant and negative effect between the interaction of firm size and capital structure on firm value. Other results found that there was no significant effect between the interaction of firm growth and capital structure on firm value.